Aquabis(3-fluorobenzoato-κO)(1,10-phenanthroline-κ(2) N,N′)copper(II) - Yin, Xin (International Union of Crystallography, 2011)
In the title compound, [Cu(C(7)H(4)FO(2))(2)(C(12)H(8)N(2))(H(2)O)], the coordination around the Cu(II) atom is square-pyramidal. The equatorial positions are occupied by two N atoms from a 1,10-phenanthroline ligand [Cu—N = 2.008 (3) and 2.019 (3) Å] and two O atoms from 3-fluorobenzoate ligands and a water molecule [Cu—O = 1.950 (2) and 1.978 (2) Å]. One O atom from another 3-fluorobenzoate ligand occupies the apical positon [Cu—O = 2.210 (2) Å]. Hydrogen bonds occur between coordinated water molecules and benzoate ligands, while O—H⋯O, C—H⋯O, C—H⋯F and π–π stacking [centroid–centroid distance = 3.731 (2) Å] interactions consolidate the crystal packing.